2008
DOI: 10.1109/tmag.2008.2002586
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric Effect of Rare Earth Nitrides

Abstract: Dy 0 5 Ho 0 5 N, Tb 0 5 Dy 0 5 N, and Tb 0 5 Gd 0 5 N were synthesized using two methods, carbothermic reduction and hot isostatic pressing, and their magnetocaloric effects were evaluated. The magnetization and specific heat of the nitrides were measured, and the magnetic entropy change 1 , adiabatic temperature change 1 and relative cooling power RCP were calculated. Values of RCP for the rare earth nitrides were larger than those of intermetallic compounds so far reported. The rare earth nitrides are promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Rare earth nitrides are very stable from the chemical point of view and do not react with hydrogen gas, in contrast with most intermetallic compounds. For an applied field of 5 T, some of these nitrides, such as HoN or ErN, present very large 211,212 ) and (D) of RN (with R=Gd, Tb, Dy, Ho and Er) after data from refs. [213][214][215][216] ΔT ad over 30 J K −1 kg −1 and around 10 K, 244 whose combined values make them as the magnetocaloric materials with the best performance in the target temperature range (see Figure 5D).…”
Section: Reviewmentioning
confidence: 96%
See 3 more Smart Citations
“…Rare earth nitrides are very stable from the chemical point of view and do not react with hydrogen gas, in contrast with most intermetallic compounds. For an applied field of 5 T, some of these nitrides, such as HoN or ErN, present very large 211,212 ) and (D) of RN (with R=Gd, Tb, Dy, Ho and Er) after data from refs. [213][214][215][216] ΔT ad over 30 J K −1 kg −1 and around 10 K, 244 whose combined values make them as the magnetocaloric materials with the best performance in the target temperature range (see Figure 5D).…”
Section: Reviewmentioning
confidence: 96%
“…Surprisingly, with the notable exception of EuS, there has been very little research in recent years focused on the magnetocaloric properties of inorganic sulfides. It is a well-known magnetocaloric material 212,234,235 behaving as a ferromagnetic semiconductor with NaCl-type crystal structure and a Curie temperature of 18 K. It displays impressive MCE figures, namely of 22 and 37 J kg −1 K −1 for 2 and 5 T, respectively, leading to RCP values of 284 and 780 J kg −1 , respectively. The associated values are 7.5 and 10.4 K, respectively.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnetism in the rare-earth nitrides has been a topic of interest since decades due to their simple crystal structure [10]. Also it was found that MCE of rare-earth (RE) nitrides is larger or comparable to intermetallic compounds in low temperature region.…”
mentioning
confidence: 99%